Improving the reactivity of hydrazine-bearing MRI probes for in vivo imaging of lung fibrogenesis. Issue 1 (14th November 2019) - Akam, Eman A.; Abston, Eric; Rotile, Nicholas J.; Slattery, Hannah R.; Zhou, Iris Y.; Lanuti, Michael; Caravan, Peter
Abstract : Improving the aldehyde-reactivity of hydrazine molecular probes translates to increased on-target accumulation in fibrotic lungs and superior visualization of disease. Abstract : Pulmonary fibrosis (PF) is the pathologic accumulation of extracellular matrix components in lung tissue that result in scarring following chronic lung injury. PF is typically diagnosed by high resolution computed tomography (HRCT) and/or invasive biopsy. However, HRCT cannot distinguish old injury from active fibrogenesis. We previously demonstrated that allysine residues on oxidized collagen represent an abundant target during lung fibrogenesis, and that magnetic resonance imaging (MRI) with a small-molecule, gadolinium-containing probe, Gd-Hyd, could specifically detect and stage fibrogenesis in a mouse model. In this work, we present an improved probe, Gd-CHyd, featuring an N, N -dialkyl hydrazine which has an order of magnitude both greater reactivity and affinity for aldehydes. In a paired study in mice with bleomycin induced lung injury we show that the improved reactivity and affinity of Gd-CHyd results in significantly higher lung-to-liver contrast, e.g. 77% higher at 45 min post injection, and slower lung clearance than Gd-Hyd. Gd-CHyd enhanced MRI is >60-fold higher in bleomycin injured mouse lungs compared to uninjured mice. Collectively, our data indicate that enhancing hydrazine reactivity and affinity towards allysine is an effective strategy to significantly improve molecular MRI probes for lung fibrogenesis.